PKM Community Empowerment and Preservation of Tourism Villages on Krisna Souvenirs in Blangsinga Village, Blahbatuh Sub-District, Gianyar District - Desak Gde Dwi Arini (Fakultas Hukum, Universitas Warmadewa, 2023)
In the Decree of the Regent of Gianyar, one of the Tourism Villages in Gianyar Regency is Saba Tourism Village, Blahbatuh District, Gianyar Regency. Saba Tourism Village has tourism businesses such as: Nature Tourism, Cultural Tourism, and Artificial Tourism. Saba Village, has five (5) Traditional Villages and eight (8) banjar Dinas. One of the traditional villages is Blangsinga Traditional Village, which has the power to manage the Blangsinga Tourism Village, with well-known tourism businesses, namely natural attractions of waterfalls and Glass Bridges. Partner Issues: 1). There is no written agreement between the Customary Village of Blangsinga Tourism Village and Krisna Souvenirs Business related to community empowerment of Blangsinga Tourism Village. And 2). There is no optimal preservation of the Tourism Village, so how to preserve the Blangsinga Tourism Village so that it is still able to attract foreign and domestic tourists to come to the Blangsinga Tourism Village. The research method used is empirical legal research, namely by collecting primary data through observation, interviews, and distributing questionnaires. After the primary data is collected, it is processed, using qualitative methods and analyzed with descriptive analytical techniques to get conclusions with accurate data. Blangsinga Tourism Village, is a tourism village that has natural attractions of waterfalls, as well as the Glass Bridge, besides that in the Blangsinga Tourism Village area there is a business by Krisna, in order to empower and preserve the Blangsinga Tourism Village.